2015
DOI: 10.1038/pr.2015.39
|View full text |Cite
|
Sign up to set email alerts
|

Combined iNO and endothelial progenitor cells improve lung alveolar and vascular structure in neonatal rats exposed to prolonged hyperoxia

Abstract: Background: Stem cells or inhaled nitric oxide (iNO) are reported to improve lung structures in bronchopulmonary dysplasia (BPD) models. We hypothesized that combined iNO and transplanted endothelial progenitor cells (EPCs) might restore lung structure in rats after neonatal hyperoxia. Methods: Litters were separated into eight groups: room air, hyperoxia, hyperoxia + iNO, hyperoxia + iNO + L-NAME, hyperoxia + EPCs, hyperoxia + EPCs + L-NAME, hyperoxia + EPCs + iNO, and hyperoxia + EPCs + iNO + L-NAME. Litters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Steudel et al (1999) found the expression and activity of both eNOS and iNOS increased in the adult rat lung following hyperoxia exposure, but Arkovitz et al (1997) found hyperoxia had differential effects on the eNOS and iNOS and hyperoxia was able to decrease eNOS activity . The reduction in eNOS expression was also confirmed by the study of Lu et al (2015). However, the study of Grisafi et al (2012) showed eNOS expression increased in hypoxia-treated rats and L-citrulline further increased eNOS expression in the lung, accompanied by the improvement of lung Arkovitz et al (1997), hyperoxia failed to increase serum NO, but resulted in a small but significant increase in NO production in the BALF.…”
Section: No and Lung Diseasesmentioning
confidence: 76%
See 1 more Smart Citation
“…Steudel et al (1999) found the expression and activity of both eNOS and iNOS increased in the adult rat lung following hyperoxia exposure, but Arkovitz et al (1997) found hyperoxia had differential effects on the eNOS and iNOS and hyperoxia was able to decrease eNOS activity . The reduction in eNOS expression was also confirmed by the study of Lu et al (2015). However, the study of Grisafi et al (2012) showed eNOS expression increased in hypoxia-treated rats and L-citrulline further increased eNOS expression in the lung, accompanied by the improvement of lung Arkovitz et al (1997), hyperoxia failed to increase serum NO, but resulted in a small but significant increase in NO production in the BALF.…”
Section: No and Lung Diseasesmentioning
confidence: 76%
“…In a study of Waldow et al (2008), they found pre-conditioning by inhaled NO (15 ppm, 10 minutes) was able to prevent hyperoxic and ischemia/reperfusion injury in adult rat lungs. In addition, Lu et al (2015) investigated the protective effects of inhaled NO in combination with endothelial progenitor cells transplantation on HALI, and results showed this was able to improve lung alveolar and vascular structure in neonatal rats with prolonged hyperoxia exposure.…”
Section: Different Uses Of Inomentioning
confidence: 99%
“…Supplemental ECFC, 38 EPC, 31,41 BMDAC, 71 hAEC, 36,74 hAFSC, 33 hiPSC-derived LPC, 53 and hiPSC-derived AEC. 53 Different from this were "probably beneficial" therapies which included ECFC, 60 hAEC, 60,64,65 CB CD 34+, 44 Mononuclear CD 34+, 46,47 and BM Ckit+.…”
Section: Summary Of Authors' Conclusion Regarding Interventionsmentioning
confidence: 99%
“…In a rat model, hyperoxia exposure led to air space enlargement, loss of lung capillaries and low expression of vascular endothelial growth factor (VEGF) and endothelial cell nitric oxide synthase. Transplanted endothelial progenitor cells, when combined with iNO, resulted in improved alveolarisation, microvessel density and upregulation of VEGF and eNOS proteins 56. Bronchioalveolar stem cells are an adult lung stem cell population capable of self-renewal and differentiation in culture 57.…”
Section: Xenonmentioning
confidence: 99%